2004
DOI: 10.1521/aeap.16.6.487.53789
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary HIV Testing, Disclosure, and Stigma Among Injection Drug Users in Bali, Indonesia

Abstract: Recently, large increases have been noted in injection drug use and HIV prevalence in Indonesia. Because voluntary HIV counseling and testing can play an important role in HIV prevention, it is important to understand factors related to its use. The objective of this study was to identify factors related to the use of voluntary HIV testing among drug users. In-depth interviews were conducted with a sample of 40 drug users in the Denpasar area of Bali, Indonesia. Drug users may be interested in testing if they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 8 publications
3
43
0
4
Order By: Relevance
“…In addition, less willingness to undergo and acceptance of HIV testing may be related to the fear of stigma and discrimination. Studies in Indonesia (Ford, Wirawan, Sumantera, Sawitri, & Stahre, 2004) and China (Ma et al, 2007) have indicated that stigma and discrimination as a result of testing positive for HIV were the major reasons for a lack of willingness to undergo HIV testing. Rogers et al (2006) also reported that even individuals who were willing to undergo HIV testing were concerned about confidentiality and negative reactions from their friends and relatives in the community.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, less willingness to undergo and acceptance of HIV testing may be related to the fear of stigma and discrimination. Studies in Indonesia (Ford, Wirawan, Sumantera, Sawitri, & Stahre, 2004) and China (Ma et al, 2007) have indicated that stigma and discrimination as a result of testing positive for HIV were the major reasons for a lack of willingness to undergo HIV testing. Rogers et al (2006) also reported that even individuals who were willing to undergo HIV testing were concerned about confidentiality and negative reactions from their friends and relatives in the community.…”
Section: Discussionmentioning
confidence: 99%
“…However, in HIV/ AIDS cases, especially in Indonesia, stigma is a big issues, fear of being discriminated resulted for patients with HIV/AIDS tend not to disclose their HIV status to others, not use condoms to prevent HIV transmission, and not seek and receive treatment for HIV, which would affect their quality of life (Ford et al, 2004). Hence, home based care can be one of consideration to design effective palliative care for patients with HIV/AIDS in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…• По данным обследования среди потребителей инъекционных наркотиков в Индонезии, около 40% опрошенных указали, что потребители наркотиков избегают тестирования на ВИЧ из-за стигматизации [4].…”
Section: профилактика и тестированиеunclassified
“…Представители этих групп зачастую не обращаются за необходимыми услугами, или откладывают такое обращение из страха быть "разоблаченными", униженными и/или боясь изменений в отношении со стороны медицин-ских работников и, в некоторых случаях, опасаясь судебного преследования и тюремного заключения. [4,23,24].…”
Section: усиление последствий в социально уязвимых группахunclassified